Towards developing digital collaboration capabilities : Case study on the Distributor-Supplier relationship in the metal industry - Virtanen, Tommi (My University, 2017)
The aim of this thesis is to explore how digital collaboration capabilities should be developed in conservative and complex supply chain environment which consists of large companies with inflexible structures, systems and processes. This study is a single-case study that focuses on Distributor-Supplier relationship in metal industry. Exploitation of value networks with advanced technology plays important role in supply chain business. Digital collaboration capabilities are critical capabilities to digitize and increase the value in supply chain networks by decreasing costs and enhancing the operations. Traditional operations cannot meet the requirements of digitalization. Companies are required to develop their digital collaboration capabilities to create and capture the value from the networks. The theoretical background of the study includes literature about digital collaboration in supply chain network and dynamic capabilities theory. The synthesis of digital collaboration development framework is presented in the end of the theory section. The methodology of this study is based on a qualitative case study. Empirical data was collected with semi-structured interviews. The interview participants were chosen by the assignment distributor company. According to the main findings, inflexible structures and systems with conservative atmosphere set up barriers and hinder the development of digital collaboration capabilities. To develop digital collaboration capabilities companies are required to manage and develop its data synchronization and development of digital solutions and tools capabilities. Data synchronization capabilities built base for digital solutions and tools development. Appropriate management of digital tools and solutions development enables cost-effective and innovative solutions which provide competitive advantage for collaborative partners. Management of digital collaboration development consisting data synchronization capabilities and management of digital tools and solutions development provide basis for exploiting value networks with advanced technology solutions. Further research could examine in detail data synchronization capabilities and management of digital tools and solutions for deeper understanding and knowledge.